Repression of human papillomavirus oncogene expression under hypoxia is mediated by PI3K/mTORC2/AKT signaling - Boßler, Felicitas Martha; Rösl, Frank; Krijgsveld, Jeroen; Hoppe-Seyler, Karin; Hoppe-Seyler, Felix (mBio, 2019)
Hypoxia is linked to therapeutic resistance and poor clinical prognosis for many tumor entities, including human papillomavirus (HPV)-positive cancers. Notably, HPV-positive cancer cells can induce a dormant state under hypoxia, characterized by a reversible growth arrest and strong repression of viral E6/E7 oncogene expression, which could contribute to therapy resistance, immune evasion and tumor recurrence. The present work aimed to gain mechanistic insights into the pathway(s) underlying HPV oncogene repression under hypoxia. We show that E6/E7 downregulation is mediated by hypoxia-induced stimulation of AKT signaling. Ablating AKT function in hypoxic HPV-positive cancer cells by using chemical inhibitors efficiently counteracts E6/E7 repression. Isoform-specific activation or downregulation of AKT1 and AKT2 reveals that both AKT isoforms contribute to hypoxic E6/E7 repression and act in a functionally redundant manner. Hypoxic AKT activation and consecutive E6/E7 repression is dependent on the activities of the canonical upstream AKT regulators phosphoinositide 3-kinase (PI3K) and mechanistic target of rapamycin (mTOR) complex 2 (mTORC2). Hypoxic downregulation of E6/E7 occurs, at least in part, at the transcriptional level. Modulation of E6/E7 expression by the PI3K/mTORC2/AKT cascade is hypoxia specific and not observed in normoxic HPV-positive cancer cells. Quantitative proteome analyses identify additional factors as candidates to be involved in hypoxia-induced activation of the PI3K/mTORC2/AKT signaling cascade and in the AKT-dependent repression of the E6/E7 oncogenes under hypoxia. Collectively, these data uncover a functional key role of the PI3K/mTORC2/AKT signaling cascade for viral oncogene repression in hypoxic HPV-positive cancer cells and provide new insights into the poorly understood cross talk between oncogenic HPVs and their host cells under hypoxia. - IMPORTANCE Oncogenic HPV types are major human carcinogens. Under hypoxia, HPV-positive cancer cells can repress the viral E6/E7 oncogenes and induce a reversible growth arrest. This response could contribute to therapy resistance, immune evasion, and tumor recurrence upon reoxygenation. Here, we uncover evidence that HPV oncogene repression is mediated by hypoxia-induced activation of canonical PI3K/mTORC2/AKT signaling. AKT-dependent downregulation of E6/E7 is only observed under hypoxia and occurs, at least in part, at the transcriptional level. Quantitative proteome analyses identify additional factors as candidates to be involved in AKT-dependent E6/E7 repression and/or hypoxic PI3K/mTORC2/AKT activation. These results connect PI3K/mTORC2/AKT signaling with HPV oncogene regulation, providing new mechanistic insights into the cross talk between oncogenic HPVs and their host cells.